It Starts with Us: Collaboration for Improved Public Health - Findlen, Ursula M. (Seminars in Hearing, 2025)
Hearing healthcare has always been multidisciplinary and collaborative in nature. The advent of over-the-counter (OTC) hearing aids has introduced a new partnership opportunity between audiologists and pharmacists. This article will apply public health aspects of hearing loss in adults to models of interprofessional partnership and healthcare through didactic case examples. Resources specific to building a professional community to support the needs of adults with hearing loss will be highlighted.
Keywords: OTC hearing aid; hearing loss; case discussions; audiology; pharmacy